Pengaruh Penggunaan Modal Kerja Terhadap Peningkatan Profitabilitas (Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Dibursa Efek Indonesia Periode Tahun 2018-2021) - Deby Handayani (CV. ITTC INDONESIA, 2023)
This study aims to examine the effect of using working capital consisting of cash turnover and receivables turnover on profitability measured using the Return On Assets Ratio (ROA) scale. The research sample is on food and beverage sub-sector companies listed on the Indonesia Stock Exchange from 2018-2021. The data used in this study are in the form of financial statements of food and beverage companies, namely statements of financial position and income statements. The sampling technique is using purposive sampling method, quantitative research and testing using multiple analysis methods using SPSS software version 23. Based on analyzed that cash turnover and receivables turnover have an effect of 16.3% on the increase in Return On Assets (ROA) in the food and beverage sub-sector listed on the Indonesian Stock Exchange.